Evaluation of Treatment of Bulk Mercury and High Mercury Surrogate Waste - Mary Cunningham (The Minerals, Metals and Materials Society, 2003)
The EPA and DOE have collaborated on a series of studies to evaluate the effectiveness of treatment technologies at stabilizing bulk elemental mercury and wastes containing high concentrations (i.e., with greater than 260 mglkg total mercury) and multiple forms of mercury. The data from these treatment demonstrations are intended to help EPA to determine if regulatory revisions to allow a stabilization alternative for high-mercury subcategory wastes are warranted. In addition to mercury-contaminated wastes, the disposal of bulk elemental mercury is of concern because of the excess quantity of mercury in the Defense Logistics Agency (DLA) stockpile, as well as other potential sources of excess elemental mercury. The studies evaluated the effectiveness of several technologies at: I) stabilization of mercury in a "hard-to-treat" matrix; and 2) conversion of elemental mercury into a stable waste form for disposal. A surrogate waste was designed for the study on high-mercury wastes, which included an organic form of mercury, elemental mercury, and several mercury salts in an inorganic matrix. The surrogate waste and the bulk elemental mercury were treated by the vendors, and the treated waste forms evaluated for mercury Icachability, using both the TCLP and an automated, constant-pH leaching protocol. Constant pH leaching was conducted at pH 2,4,6,8 10 and 12 for 14 days at each pH. The leaching data demonstrate that the stability of the mercury in three treated waste forms varies widely across the pH range tested. Clearly, the stability of mercury in these treated waste forms will be highly dependant on the disposal conditions. The combination of site-specific disposal conditions and appropriate treatment technology must be considered as decisions are made about disposal of high-mercury wastes.